Effectiveness of highly purified urofollitropin treatment in patients with idiopathic azoospermia before testicular sperm extraction. Issue 1 (February 2018) - Cocci, Andrea; Cito, Gianmartin; Russo, Giorgio I.; Falcone, Marco; Capece, Marco; Timpano, Massimiliano; Della Camera, Pier Andrea; Morselli, Simone; Tasso, Giovanni; Morelli, Girolamo; Morgia, Giuseppe; Minervini, Andrea; et al.
Introduction: Recent evidences demonstrated that male factor alone is responsible for about 30% cases of infertility. Human follicle-stimulating hormone (hFSH) has been introduced to increase sperm concentration, spermatogonial population, or both natural or assisted pregnancy rates (PRs) in oligozoospermic subjects with normal concentrations of gonadotropins. Methods: Fifty infertile men affected by idiopathic azoospermia were enrolled in this study, after undergoing medical history, physical and clinical examination, baseline semen parameters and hormonal plasma concentrations. Inclusion criteria were infertility for at least 2 years, idiopathic azoospermia, FSH <12 mIU/ml. Twenty-five patients were allocated to treatment with hFSH three times/week per 3 months (Fostimon), and 25 patients underwent just testicular sperm extraction (TESE) without medical treatment. All patients underwent, after 3 months, assisted reproduction techniques (ARTs) with TESE. The primary outcome was represented by the differences in the sperm retrieval rate (SRR) between groups, while the secondary outcomes were the differences in PR and fertilization rate (FR). Results: We observed a PR of 15% (3/25) and 28% (7/25) in control and treated group, respectively. SRR after medical treatment and ART was 24% (6/25), while in the control group was 12.5% (2/25). The sperm in the ejaculate of five patients (20%) after medical treatment exhibited a mean concentration of 0.9 million/ml and a mean motility of 12%. The FR was significantly greater in the treatment group with respect to the control group, 30% and 20%, respectively. Conclusions: FSH treatment showed greater efficacy rather than control by increasing the rate of PR and FR in azoospermic patients who underwent TESE.